2018
DOI: 10.24201/eg.v4i0.218
|View full text |Cite
|
Sign up to set email alerts
|

Mujeres y cooperativismo en Cuba hoy. Un estudio de redes sociales

Abstract: Resumen:La creación de las Cooperativas No Agropecuarias (CNA) en Cuba está promoviendo cambios en su estructura social. Tanto mujeres como hombres se han incorporado a este nuevo espacio de oportunidades laborales, de manera que resulta pertinente analizar las ventajas y los retos que esto plantea para los cooperativistas, en especial para las mujeres, respecto a su inserción laboral y social. Para la presente investigación se utilizó un diseño mixto que incluyó la aplicación de un cuestionario sobre redes so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In the literature review, four central topics were identified as guiding the exploration of the hinderers and facilitators of care cooperatives in the interviews: gender differences in access to care-related jobs (FUNDACIÓN MUJERES, 2011; de Arce, 2017;Caballero, 2018), the characteristics of the labor market and the levels of informality in each context (ILO, 2018;Berniell et al, 2021), and the concept of "decent work" used as horizon in the development of care cooperatives in relation with the political and economic context of each country (ILO, 2015;Matthew & Bransburg, 2017;Matthew, 2017Flanders, 2014Nembhard, 2014;Poo & Conrad, 2015;Savitch-Lew, 2015;Montero Vargas et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature review, four central topics were identified as guiding the exploration of the hinderers and facilitators of care cooperatives in the interviews: gender differences in access to care-related jobs (FUNDACIÓN MUJERES, 2011; de Arce, 2017;Caballero, 2018), the characteristics of the labor market and the levels of informality in each context (ILO, 2018;Berniell et al, 2021), and the concept of "decent work" used as horizon in the development of care cooperatives in relation with the political and economic context of each country (ILO, 2015;Matthew & Bransburg, 2017;Matthew, 2017Flanders, 2014Nembhard, 2014;Poo & Conrad, 2015;Savitch-Lew, 2015;Montero Vargas et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The percentages of involvement in management bodies, representation, and positions played by men and women inside cooperatives nevertheless differ significantly from one another. According to several studies, these environments exhibit smaller gender inequalities than other work contexts (FUNDACIÓN MUJERES, 2011; de Arce, 2017;Caballero, 2018). According to Crompton & Sanderson (1990), women's involvement in cooperatives follows a similar pattern depending on the kinds of activities they engage in.…”
Section: Gender Inequality and Cooperativesmentioning
confidence: 99%
See 1 more Smart Citation